Outcome of Subtrochanteric Femur Fractures Treated by Proximal Femoral Nail in a Tertiary Care Hospital - Rahman Rasool Akhtar, Riaz Ahmed, Omair Ashraf, Rahman Rasool Akhtar, Riaz Ahmed, Omair Ashraf (Journal of Rawalpindi Medical College, 2022)
Background: Subtrochanteric femoral fractures are challenging for surgeons, as it has strong collapsing forces at fracture site.The management of sub-trochanteric fractures, especially nonunion is challenging.Proximal Femoral Nail can be helpful in achieving high success rate. But there was a lack of local evidence. Objective: To determine the Outcome of Subtrochanteric Femur Fractures Treated by Proximal Femoral Nail in a Tertiary Care Hospital. Material and methods: This prospective study was conducted from 1stJuly 2017 to 30th June 2019. The inclusion criteria were all the patients of both genders above 16 years of age presented to emergency department with subtrochanteric fractures of the femur. Exclusion criteria included pathological fractures, fractures in children, old neglected fractures and multiple fractures. Radiographs were taken and all the patients were classified according to Seinshemers classification. All the patients underwent internal fixation with Proximal Femoral Nail. The outcome of all patients were assessed by using Modified Harris Hip Score. Results: A total of 110 patients were included in the study. Mean age of patients was 30.05±8.59 years. 81 (73.63 %) patients were males and 29 (26.36%) were females. According to Seinshemers classification, we had 54 patients with Type II fracture, 35 patients with Type III fracture, 19 patients with Type IV fracture and 02 patients with Type V fracture. Mean duration of hospital stay was 06 days and mean time of full weight bearing was 12 weeks. In our study, excellent results were found in 71 patients (64.5%), good results in 28 patients (25.4%), fair results in 06 patients (5.4%) and poor results in 03 patients (2.7%).02 patients were lost in follow up. The mean Harris Hip score was 93.5± 5.42. 14 patients (12.7%) had minor complications including 06 patients with Superficial wound infections, 03 patients with Deep infection, 01 patient with Deep vein thrombosis and 04 patients had Fracture from distal tip of nail. All the fractures unite within 6 months period and no implant failure was observed. Conclusion: Proximal Femoral Nail is a good choice implant for the fixation of subtrochanteric femur fractures leading to high rate of union, fewer implant related complications and excellent functional outcome. Key words: Subtrochanteric, Femur fracture, Proximal Femoral Nail, Modified Harris Hip Score, Seinshemers classification, Complications